2020
DOI: 10.1038/s41598-020-59378-5
|View full text |Cite
|
Sign up to set email alerts
|

Individual variation in the attribution of incentive salience to social cues

Abstract: Research on the attribution of incentive salience to drug cues has furthered our understanding of drug self-administration in animals and addiction in humans. The influence of social cues on drug-seeking behavior has garnered attention recently, but few studies have investigated how social cues gain incentive-motivational value. In the present study, a Pavlovian conditioned approach (PCA) procedure was used to identify rats that are more (sign-trackers; STs) or less (goal-trackers; GTs) prone to attribute ince… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…Most of the time animal studies control for auditory input in relation to oxytocin. At the time of writing this review, there is not enough information about the changes due to said input considering this neuropeptide, but it seems that the relationship between oxytocin and auditory input is species-dependent, namely, SD rats, wolves (a strong hierarchical order), cats (somewhat owner-dependent response), and zebra finch (mesotocin-spatial location of birds among each other) behaved differently ( Watts et al, 2022 ; Baran et al, 2016 ; Fitzpatrick and Morrow, 2020 ; Hosgorler et al, 2020 ; Nagasawa et al, 2022 ; Wirobski et al, 2023 ). Humans commonly use singing in many rituals, and it is part of every culture throughout the world.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the time animal studies control for auditory input in relation to oxytocin. At the time of writing this review, there is not enough information about the changes due to said input considering this neuropeptide, but it seems that the relationship between oxytocin and auditory input is species-dependent, namely, SD rats, wolves (a strong hierarchical order), cats (somewhat owner-dependent response), and zebra finch (mesotocin-spatial location of birds among each other) behaved differently ( Watts et al, 2022 ; Baran et al, 2016 ; Fitzpatrick and Morrow, 2020 ; Hosgorler et al, 2020 ; Nagasawa et al, 2022 ; Wirobski et al, 2023 ). Humans commonly use singing in many rituals, and it is part of every culture throughout the world.…”
Section: Discussionmentioning
confidence: 99%
“…Territorial behavior was positively related to oxytocin and glucocorticoid release, and separation from the pack increased glucocorticoid concentrations, indicating that social and environmental factors, such as returning home or social reunions, can differently affect oxytocin levels in animals too ( Wirobski et al, 2023 ). Consequently, it is suggested that the level of oxytocin should be measured at different time points ( Fitzpatrick and Morrow, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the time animal studies control for auditory input in relation to oxytocin. At the time of writing this review, there is not enough information about the changes due to said input considering this neuropeptide, but it seems that the relationship between oxytocin and auditory input is species-dependent, namely, SD rats, wolves (a strong hierarchical order), cats (somewhat owner-dependent response), and zebra finch (mesotocin-spatial location of birds among each other) behaved differently (Watts et al, 2022;Baran et al, 2016;Fitzpatrick and Morrow, 2020;Hosgorler et al, 2020;Nagasawa et al, 2022;Wirobski et al, 2023). Humans commonly use singing in many rituals, and it is part of every culture throughout the world.…”
Section: Auditorymentioning
confidence: 99%
“…Territorial behavior was positively related to oxytocin and glucocorticoid release, and separation from the pack increased glucocorticoid concentrations, indicating that social and environmental factors, such as returning home or social reunions, can differently affect oxytocin levels in animals too (Wirobski et al, 2023). Consequently, it is suggested that the level of oxytocin should be measured at different time points (Fitzpatrick and Morrow, 2020).…”
Section: Social Context 451 Oxytocin As a Reward Related To Sports In...mentioning
confidence: 99%